Influencia de la capacitación del personal en la gestión de comercialización del maracuyá de productores de Quñijallpa de Chao, 2018 - González Sánchez, Katterine Yeraldin (2020)
This research work is for the purpose of studying the AGRICULTURAL COOPERATIVE QUÑIJALLPA; which is located in chao district, Virú Province, La Libertad and its main objective is to determine the influence of staff training on the marketing management of the Quñijallpa producers' passion fruit. It must be taken into account that the Agricultural Cooperative groups to date 34 producers of passion fruit, which have as Cooperative 100 hectares of agricultural land. On the visits to the cooperative an-interview was made to the mánager Nataly Rubio Poma, where I report that there was a deficiency in the training of producers having influence when they marketed the passion fruit, in addition for the collection of data has been applied surveys to the partners. The research problem concerns the following question How does staff training influence the marketing management of the passion fruit of Producers of Quñijallpa de Chao, 2018? What a hypothesis is: Staff training has a favorable influence on the marketing management of the chao Quñijallpa producers' passion fruit, 2018. Before developing the necessary solution alternatives that will be of great use to the producers of passion fruit in Chao, a bibliographic review will be carried out for this research work, where it can be known that staff training has a favorable influence on the marketing management of the fruit of producers of Quñijallpa de Chao, 2018.